Prediction of the mechanical behavior of double walled-CNTs using a molecular mechanics-based finite element method: Effects of chirality. (June 2016) - Doh, Jaehyeok; Lee, Jongsoo
Highlights: Description of nonlinear behaviors of CNTs based on Morse potential energy model. Evaluation of mechanical properties of SWCNTs/DWCNTs using molecular mechanics-based finite element method. Evaluation of mechanical properties of DWCNTs with the combination of Armchair–zigzag and zigzag–armchair. Validation of the proposed finite element model that is formulated with nonlinear beam elements. Comparison of Young's modulus, ultimate stress and strain with other research results. Abstract: Carbon nanotubes (CNTs) have distinct features in their remarkable mechanical, electrical, thermal, and chemical properties. However, material properties of CNTs can often not be validated due to experimental limitations. In this study, we developed finite element models of single-walled carbon nanotubes (SWCNTs) and double-walled carbon nanotubes (DWCNTs) based on molecular mechanics theory to evaluate mechanical properties such as Young's modulus, ultimate strength, and strain in accordance with chirality. We performed tensile analyses with armchair/zigzag SWCNTs and armchair–zigzag/zigzag–armchair DWCNTs composed of nonlinear beam elements. We validated the proposed FE model of SWCNTs by comparing ultimate stress and strain with conventional approaches.